Model Edukasi Partisipatif Zona Selamat Sekolah untuk Penguatan Literasi dan Perilaku Keselamatan Lalu Lintas Siswa - Fitridawati Soehardi; Hendri Rahmat; Marlaily Idris; Yohana Pinta uli Panjaitan; Rezky Aulia Ramadhani (LPPPM STAI Darul Hikmah Bangkalan, 2026)
This community service program strengthened road safety literacy and safe behavior among school community members at Witama School, Pekanbaru, through a participatory School Safety Literacy Model based on the School Safety Zone. The program responded to the school need for practical traffic safety education, clearer understanding of signs and markings, safer crossing habits, and a simple school follow up mechanism. The model consisted of five connected components: risk mapping, traffic sign literacy, guided safe crossing practice, school commitment, and program continuity. Activities involved 95 students through coordination with the school, field observation, interactive education, group discussion, traffic sign simulation, safe crossing practice, reflection, and handover of educational outputs. The outputs received by the school included a road safety literacy module, traffic sign posters, a simple risk map around the school gate, a teacher monitoring checklist, presentation materials, and recommendations for pick up and drop off arrangement. A short pre and post activity quiz was used only as a learning reflection tool. The average score increased from 52.37 before the activity to 95.74 after the activity, showing improved understanding of School Safety Zone concepts, traffic signs, safe crossing steps, and school safety culture. The program also produced a sustainability plan through teacher supervision, repeated use of educational media, and routine reminders during school arrival and dismissal times. This program shows that community service in school traffic safety becomes more useful when it leaves practical tools, builds school participation, and creates a follow up mechanism after the activity ends